In-silico Development of Novel Plasmid Construct for Production of Recombinant Chitinase in Saccharomyces cerevisiae - Hossain, Sk Amir; Rima Akter (Journal of Science and Technology, 2024)
This study presents the design and potential application of novel plasmid constructs for chitinase enzyme production in Saccharomyces cerevisiae. Using advanced molecular techniques in recombinant DNA technology, we constructed two unique plasmids—pESC-TRPGAL1, 10Chitinase2 and pESC-TRPPHO5chitinase2—specifically engineered to facilitate the insertion of the Candida albicans chitinase-encoding gene (CHT3) into yeast. The plasmid pESC-TRPGAL1, 10Chitinase2 incorporates a genetic cassette with GAL1 and GAL10 strong bidirectional promoters, a signal sequence, and a 6xHis tag. Conversely, pESC-TRPPHO5chitinase2 features the GAL1 promoter in one direction and the PHO5 promoter in the other, along with a signal sequence and 6xHis tag. The plasmid design enables the targeted expression of recombinant chitinase when transformed into S. cerevisiae, with functionality and activity potentially assessable via selective culture with 1–2% chitin media. This work emphasizes the innovation in plasmid construction for recombinant chitinase expression and establishes the groundwork for experimental validation, which will focus on assessing the activity of enzyme and thermostability relative to wild-type C. albicans chitinase.